Positive psychology and appreciative inquiry in higher education - Mather, Peter; Hulme, Eileen (New directions for student services ;, 2013)
Given the shared interest between higher education and positive psychology in developing healthy and productive human beings, this issue explores how this new subdiscipline of psychology can contribute to the mission of higher education. It presents a variety of strategies for bolstering student learning and development. The authors also draw from appreciative inquiry, which, like positive psychology, is based on studying strengths, but focuses on organizational rather than individual performance. During a time of daunting challenges, positive psychology and appreciative inquiry can help to l.